Short-Term Comfort Responses Associated With the Use of Eyelid Cleansing Products to Manage Demodex folliculorum. (November 2018) - Ngo, William; Jones, Lyndon; Bitton, Etty
Abstract : Purpose: To quantify the discomfort over time of various eyelid cleansers against Demodex . Methods: This was a prospective, randomized, controlled, crossover, open-label study that enrolled 26 participants. The cleansers used in this study were Biotissue Cliradex (CD), OCuSOFT Lid Scrubs Plus (OP), OCuSOFT OUST Demodex Swabstix (ODS), TheraTears Theralid (TT), NovaBay Avenova (NA). Bausch+Lomb Sensitive Eyes Plus saline was used as a control. Participants were asked to close their eyes as the product was gently rubbed (10 cycles of gentle lateral motion) into the eyelashes. Participants verbally rated their discomfort (0 = no discomfort, 10 = maximum tolerable discomfort) every 15 sec for the first 5 min, and every 30 sec for 5 min after, for a total of 10 min. The order of products used was randomized, and washout period between cleansing was 48 hr. Results: Twenty-five participants completed the study (mean age=26±6). There was no significant difference in discomfort scores at pre-application. The discomfort levels of saline, OP, and NA over the 10-min period were not significantly different than their pre-application discomfort at all time points (all P ≥0.99). The discomfort of CD was significantly higher than pre-application levels between t=15 sec and t=180 sec (all P ⩽0.01), with maximum median (interquartile range [IQR]) discomfort of 3.0 (5.0) occurring at t=45 sec. The discomfort of TT was significantly higher than pre-application levels between t=45 and t=90 (all P <0.02), with maximum median (IQR) discomfort of 1.0 (1.5) occurring at t=75 sec. The discomfort of ODS was significantly higher than pre-application levels starting from t=60 sec and onward, with maximum median (IQR) discomfort of 6.0 (5.0) occurring at t=300 sec. Conclusion: Of the cleansers used in this study, the ones that induced significant discomfort were CD, TT, and ODS. The results from this study may help clinicians educate patients about what to expect when approaching the topic of eyelid Demodex treatment.